An integration of kano model and quality function deployment technique - a case study using sport earphone. (January 2019) - Aliyu, R; Arifin, A M T; Haq, R H A; Hassan, M F; Rahman, M N A; Ismail, A E; Rahim, M Z; Ibrahim, M R; Azlan, M A; Ahmad, M S; Taib, I; Ismail, R
Abstract: Product modification is predetermined as another important approach to capture market demand and competitor situation. Development and marketing strategy of product with modified features by designer as an attractive element for consumers. Therefore, this paper discusses an approach and process that would help the product development team to develop an innovative product with attractive qualities. Customer requirement and satisfaction evaluation can be accomplished via various methods. In this study, the integration between Kano Model and Quality Function Deployment was identified to evaluate the customer satisfaction based on the proposed product. A survey was conducted among 80 athletes to determine the possibility criterion for improvement on an existing sport earphone, in term of various aspect such as design, material used, appearance and accessories. After that, the result was interpreted into a Kano questionnaire and answered by 80 respondents. Consequently, it was analyzed and applied in the House of Quality matrix. At the end of this study, it was found that both methods were able to prioritize the modification of essential features to be executed into the sport earphone which can be profitable in developing a product in such a way that maximum customer satisfaction can be achieved. Therefore, an integration of Kano Model and Quality Function Deployment, can be a great assistance when it comes to understanding the needs of users, satisfaction of users who use the sport earphone at long period, in order to give more comfort for consumers.